Towards better utilisation of non-conventional feed sources by sheep and goats in some African and Asian countries - Ben Salem H.; Nefzaoui A.; Makkar H.P.S. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
Chronic feed deficits represent a major constraint to animal production in many developing countries. Expanding the feed resource base through utilisation of non conventional feed resources is a compelling task. These are still not well integrated into livestock feeding due to three reasons: (i) the unbalanced supply of nutrients; (ii) the presence of undesirable compounds; and (iii) the difficulties to store. Several technologies have been developed to overcome this problem. Ensiling conserves the feeding value of some agro-industrial by-products, but the adoption of this technique is still limited. Feed blocks are becoming popular as a balanced supplement for animals. Numerous multipurpose browse trees and shrubs have potential in agroforestry systems. It is possible to increase the nutritive value of tannin-rich browse with compounds such as polyethylene glycol. Additionally, tannins could be used advantageously to improve production, through reduction in protein degradation of many oil seed cakes-meals in the rumen.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)